Gallbladder Cancer Cell-Derived Exosome-Mediated Transfer of Leptin Promotes Cell Invasion and Migration by Modulating STAT3-Mediated M2 Macrophage Polarization. (24th January 2022) - Zhao, Songling; Liu, Yunxia; He, Linhai; Li, Yuehua; Lin, Ke; Kang, Qiang; Liu, Lixin; Zou, Hao
Abstract : Tumor-associated macrophage (TAM) is a major component of tumor microenvironment (TME) and plays critical role in the progression of cancer metastasis. However, TAM-mediated regulation in gallbladder cancer (GBC) has not been fully characterized. Here, we found that exosomes derived from GBC cell polarized macrophage to M2 phenotype, which then facilitated the invasion and migration of GBC cells. We discovered that leptin was enriched in GBC cell-derived exosomes. Exosomal leptin levels promoted invasion and migration of GBC-SD cells. The inhibition of leptin not only attenuated M2 macrophage of polarization but also inhibited the invasive and migratory ability of GBC cell. In addition, GBC-SD cell-derived exosomal leptin induced M2 polarization of macrophage via activation of STAT3 signal pathway. Taken together, our results suggested that GBC cells secrete exosome-enclosed leptin facilitated cell invasion and migration via polarizing TAM.